Analysis of Needs for E-Book Development for MPASI Training - Fatmala, Anggi; Widyastono, Herry; Sukmawati, Fatma (Universitas Sebelas Maret, 2023)
E-books are effective and responsive learning media to the demands of trainees in obtaining accurate, structured and easily accessible information about complementary foods. This study aims to identify needs in the context of developing a digital media product in e-book format. This research meth-od is a qualitative descriptive method. The research subjects consisted of trainers or training instructors. The data collection techniques consisted of in-terviews and observations followed by the instruments, namely interview sheets and observation sheets. Data analysis techniques used descriptive by providing an overview of research findings. The results of this research indi-cate that during the training activities, no media or materials were provided for the trainees to study independently other than posters containing a sum-mary of the material, so they tended to have difficulty understanding materi-al about making complementary foods. Even though the residents were very enthusiastic about participating in the training activities. Therefore, an inno- vation is needed in providing knowledge to training participants, one of which can be done by developing an e-book containing training materials that can be accessed at any time by training participants. It is hoped that through this research innovation will emerge that can make it easier for train-ees to better understand material about making complementary foods.